504 Comparison of cardiovascular risk scores to predict anthracycline-induced cardiotoxicity in early breast cancer patients. (8th December 2021) - Solfanelli, Giorgio; Bianchini, Giulia; Petrungaro, Mattia; Reale, Simone; Lanza, Oreste; Ferrera, Armando; Tini, Giacomo; Piras, Marta; Pellegrini, Patrizia; Tocci, Giuliano; Battistoni, Allegra; Volpe, Massimo
Abstract: Aims: Cardiovascular (CV) toxicities related to chemotherapy have been reported with increasing frequency. Thus, latest cardio-oncology guidelines focused on the importance of a baseline CV risk assessment before starting a potentially cardiotoxic regimen, in order to identify individuals at greater risk of developing CV toxicities and to prevent them. Despite these recommendations, there are still no validated systems to predict cardiotoxicity risk in oncological patients. The aim of the present study was to compare the average risk assessed by conventional CV risk scores (SCORE, QRISK2, ASCVD) and two recently developed cardiotoxicity risk scores ( Baseline cardiovascular risk stratification proformas, Multivariable prediction model for major adverse cardiovascular events after early stage breast cancer ) in a cohort of 41 (100% female; mean age 52.9 ± 11) early breast cancer (EBC) patients treated with epirubicin and to investigate the relationship between CV and cardiotoxicity risk and the rate of CV outcome, defined as biomarkers (high sensibility Troponin I and BNP) increase during the follow-up. Results: A baseline CV risk assessment was performed in all patients before starting chemotherapy according to prespecified scores, showing a higher mean CV risk in our cohort compared to general population. Most patients were at low risk of developing cardiotoxicity according to prespecified scores. During the follow-up (mean 221 ± 75 days), the primary outcome occurred in 9.8% ( n = 4). The average CV risk scores of patients developing the primary outcome were higher than the controls according to both conventional and cardiotoxicity risk scores (Figure 1). The QRISK2 achieved the best ratio cases average score / controls average score ( r = 3) and the ROC curve confirmed QRISK2 as the best CV risk score to predict the outcome in our cohort, reaching the highest sensitivity and specificity (Figure 2). Conclusions: In a cohort of young patients affected by EBC the mean CV risk is higher than the general young female population according to traditional CV risk scores. Moreover, patients developing the primary outcome during the Follow-up were those at higher CV risk and high risk of cardio toxicity. Surprisingly the best score to predict the incidence of outcome was the QRISK2, confirming the crucial role of baseline CV risk in cancer patients.